The Implementation of Performance-Based Budgeting and The Quality of Financial Reports on The Performance Accountability of Government Agents - Nila Aprila; Devia Rolita; Febbiana Nurhasanah (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
Performance accountability is very much needed in a government agency for tangible evidence of agency accountability for the realization of a success or failure of program implementation and the achievement of specified activities. Increased accountability can be supported by the implementation of performance-based budgeting and the quality of financial reports in achieving the success of work goals and objectives. The purpose of this study is to identify the influence of performance-based budgeting and the quality of financial reports on the performance accountability of South Bengkulu Regency government agencies. This study uses quantitative methods. Purposive sampling is used in the sampling technique. The data collection technique used a questionnaire that was tested through descriptive analysis and multiple linear regression. The population in this study amounted to 40 OPD in South Bengkulu Regency. Based on the results of data management research, it is known that performance-based budgeting and reporting systems simultaneously or partially have a significant positive effect on the performance accountability of South Bengkulu Regency government agencies.